2017
DOI: 10.1108/ijebr-03-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of entrepreneurial intentions in sustainable entrepreneurship

Abstract: Purpose The role of entrepreneurship has changed to include issues beyond economic growth. This has turned attention toward the drivers of entrepreneurial intentions across entrepreneurship types, particularly in sustainable entrepreneurship. The purpose of this paper is to examine the drivers of entrepreneurial intentions in sustainable entrepreneurship. In particular, the paper aims to extend the existing intention models to include work values and attitudes toward sustainability, thereby bringing the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
334
1
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(375 citation statements)
references
References 91 publications
(184 reference statements)
24
334
1
16
Order By: Relevance
“…In addition, control variables are included. First, we control for gender as women are found to have a more favorable evaluation of sustainability [27,46]. Furthermore, we controlled for gender, as current young social movements like Friday's for Future might indicate that young people are more concerned about the environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, control variables are included. First, we control for gender as women are found to have a more favorable evaluation of sustainability [27,46]. Furthermore, we controlled for gender, as current young social movements like Friday's for Future might indicate that young people are more concerned about the environment.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have already confirmed that the three attitudinal antecedents are also capable of explaining the appearance of sustainable entrepreneurial intention [24][25][26][27][28]. Therefore, building on the TPB and a sample of 175,280 respondents, an intention-based framework is developed to empirically investigate the impact of environmental risk exposure on the formation of sustainable entrepreneurial intention.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability-oriented entrepreneurial intentions are driven by perceived entrepreneurial desirability and attitude toward sustainability [27]. Perrini et al [23] identified that sensitivity towards a social problem fosters idea generation.…”
Section: Idea Generationmentioning
confidence: 99%
“…Sustainable and social entrepreneurship differ from conventional entrepreneurship in terms of value creation and impact [27,35]. Over time, several forms of impact measurements have been proposed, however, impact in society is a social construction, involving different stakeholders, so it is not possible to establish a unique standard.…”
Section: Venture Launch and Business Exploitationmentioning
confidence: 99%
“…Over the past decade, a vast amount of scholarly work has examined various aspects of sustainable entrepreneurship, including sustainable entrepreneurs' (SEs') intention and motivation [12][13][14][15][16], SEs' competency [17][18][19], SEs' values [20], SEs' knowledge [5,21], sustainable entrepreneurial opportunity [1,2,[22][23][24], the context for SE [9,[25][26][27][28], success factors for SE [29,30], ways to promote SE [31][32][33][34][35], etc. Although prior studies are insightful, they mainly focus on individual-and/or organization-level factors, albeit the fact that most startups are launched with a group of people [36].…”
Section: Pacheco Et Al (2010) Qualitativementioning
confidence: 99%